1991
DOI: 10.1111/j.1365-2125.1991.tb05508.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of pharmacokinetic interaction between nifedipine, sparteine and phenytoin in man.

Abstract: Nifedipine, sparteine and phenytoin were administered orally to eight healthy subjects separately and as a 'cocktail' on four different occasions to investigate any kinetic interactions. All subjects were extensive metabolizers of sparteine. After drug intake plasma and urine samples were collected up to 32 h and the concentrations of parent drugs and main metabolites were measured. Clearances and formation clearances were not significantly different after single substrate and 'cocktail' administration. Low or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A cocktail design offers several advantages through the required knowledge of drug metabolic pathways obtained in a single experimental session involving possible pharmacologic or pathophysiologic effects on enzyme induction or inhibition. Effects such as concomitant drug therapy and liver disease have been evaluated with the use of several different cocktails 2 , 3 , 4 , 5 . Another advantage with a cocktail is that environmental factors do not change during the limited time of the experiment 1 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A cocktail design offers several advantages through the required knowledge of drug metabolic pathways obtained in a single experimental session involving possible pharmacologic or pathophysiologic effects on enzyme induction or inhibition. Effects such as concomitant drug therapy and liver disease have been evaluated with the use of several different cocktails 2 , 3 , 4 , 5 . Another advantage with a cocktail is that environmental factors do not change during the limited time of the experiment 1 .…”
mentioning
confidence: 99%
“…Effects such as concomitant drug therapy and liver disease have been evaluated with the use of several different cocktails. [2][3][4][5] Another advantage with a cocktail is that environmental factors do not change during the limited time of the experiment. 1 Limitations of the cocktail strategy are mutual interactions between the drugs and the high selectivity and sensitivity of the analytic methods required to analyze several drugs and metabolites in the same sample.…”
mentioning
confidence: 99%
“…Schellens et al 42 found no significant interactions in the oxidation of nifedipine, sparteine, and phenytoin and concluded that this three‐drug cocktail can be used to simultaneously characterize the activity of multiple cytochromes. Lack of significant interactions was observed among dextromethorphan, coumarin, and mephenytoin in a three‐drug cocktail for simultaneous evaluation of CYP2C19, CYP2D6, and CYP2A6 43…”
Section: Current Status Of the Cocktail Approachmentioning
confidence: 99%
“…Patients on anticonvulsant treatment will require substantially higher doses of felodipine to achieve plasma concentrations equivalent to those in patients not taking enzymeinducing agents. [9,18] Schellens et al [25] reported the lack of a pharmacokinetic interaction between phenytoin and nifedipine. [9,18] Schellens et al [25] reported the lack of a pharmacokinetic interaction between phenytoin and nifedipine.…”
Section: Carbamazepinementioning
confidence: 99%